2003
DOI: 10.1093/humrep/deg102
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution during different gestational phases contributes to risks of low birth weight

Abstract: This study suggests that exposure to CO, PM(10,) SO(2) and NO(2) during early to mid pregnancy contribute to risks for LBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 55 publications
8
85
0
9
Order By: Relevance
“…*P Ͻ 0.05 was considered statistically significant. studies linking higher PM exposure to decreases in birth weight (2,19,30,35). This is confirmed in a similar study where mice were exposed to diesel exhaust during a portion of development (15).…”
Section: -Exposed Mice (B) C: End-systolic Volume (Esv) D: Enddiassupporting
confidence: 52%
See 1 more Smart Citation
“…*P Ͻ 0.05 was considered statistically significant. studies linking higher PM exposure to decreases in birth weight (2,19,30,35). This is confirmed in a similar study where mice were exposed to diesel exhaust during a portion of development (15).…”
Section: -Exposed Mice (B) C: End-systolic Volume (Esv) D: Enddiassupporting
confidence: 52%
“…Evidence from epidemiological studies indicates a strong association between ambient concentrations of air pollutants, including PM, and poor developmental outcomes, such as low birth weight (3,19,23) preterm birth (34,37), and intrauterine growth restriction (10,36). Animal studies have confirmed these outcomes (25,38,40,44) and shown genetic and epigenetic changes in animals maternally exposed to air pollution (32).…”
mentioning
confidence: 99%
“…438 -444 The effects of air pollution on various other birth outcomes are substantially less well established and understood. Nevertheless, there are a growing number of contemporary studies that have evaluated potential links between air pollution and birth weight, [445][446][447][448][449][450][451][452][453][454][455][456] premature birth, 449,456 -458 fetal growth, 459 -461 intrauterine mortality, 462 birth defects, 463 and lymphocyte immunophenotypes in cord and maternal blood at delivery. 464 Recent reviews of the literature dealing with air pollution and these various birth outcomes 441,442,444 generally suggest that there may be effects of ambient PM air pollution on these outcomes but that these effects are not well understood.…”
Section: Infant/birth Outcomesmentioning
confidence: 99%
“…Recent studies have further demonstrated association between ambient air pollution and adverse pregnancy outcomes, including low birth weight, preterm birth, IUGR and birth defects in China (Xu et al, 1995;Wang et al, 1997), the Czech Republic (Bobak, 2000), the United States (Ritz and Yu, 1999;Ritz et al, 2000Ritz et al, , 2002Parker et al, 2005), and Korea (Lee et al, 2003). Recent Canadian studies have also provided evidence of a negative impact of air pollution on birth outcomes (Liu et al, 2003) and respiratory health among young children (Yang et al, 2003) in Vancouver.…”
Section: Introductionmentioning
confidence: 97%